Perlindungan Hak Cipta Foto Idol K-Pop Sebagai Model Pada Sampul Buku Novel - Irene Magdalena Ebygael; Candra Hayatul Iman (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this research is to look at the protection that can be provided by law against copyright for creators and copyright holders related to K-Pop idol photos that are misused to become part of the covers of fan fiction writings based on Law Number 28 of 2014 concerning Copyright. Throughout the preparation of this paper, research procedures were used in the form of descriptive analysis from primary legal sources accompanied by secondary legal materials. In connection with the existence of regulations that discuss the prohibition of duplicating copyrighted works without the permission of the creator and/or copyright holder, then if there is a violation of these rules stated in Article 80 paragraph (1) of the Copyright Law, criminal sanctions may be imposed. in the form of imprisonment and fines as well as civil in the form of compensation for the party who was harmed by the violation.